Mitochondrial DNA diversity of wild and hatchery reared strains of Indian Lates calcarifer (Bloch) - Kumar, Prasanna; John, Akbar; Kanagasabapathy, V (Springer International Publishing, 2016)
Lates calcarifer, locally known as seabass in Asia and barramundi in Australia, is a large, euryhaline member of the family Centropomidae that is widely distributed in the Indo-West Pacific region. Its hardy nature, high tolerance to wide range physiological condition and high commercial value has made it a good candidate species for aquaculture practices. In this study we compared the mtDNA diversity of hatchery reared and wild Lates calcarifer using universal DNA barcode gene (Cytochrome Oxidase C subunit 1 gene) to assess the genetic health of L. calcarifer hatchery practices in India. Sampling stations were randomly chosen to cover both East and West coasts of India. The phylogram constructed with COI sequences (n = 88) of L. calcarifer revealed that geographic distributions of clades are not restricted to any particular sampling stations. Gene flow appeared to have transported haplotypes between the clades from their likely origins across the sampled range. Both Nucleotide (π) and haplotyte (h) diversity of wild L. calcarifer was higher in East coast samples compared to West coast samples. The comparative genetic diversity analysis assessed through COI sequences between hatchery reared and wild catches of L. calcarifer showed that the nucleotide diversity of hatchery strains was 2.7 times lesser than that of wild strains, demanding immediate action plans to restore genetic diversity in L. calcarifer hatchery practices in India.